The need of landscape gardening - Troutman, Virginia (My University, 1907)
Introduction: Since the advent of cheap and rapid transportation and verbal communication, the tendency is for the population to spread itself over more territory. Not the least of the factors in causing the popularity of suburban residence is the opportunity thus afforded of surrounding one's home with out-door beauty. We are just beginning to realize what real country life means. A home should include the beautiful as well as the useful. However, this does not necessarily imply, as many people think, the accumulation of useless articles of so called ornamental value. Landscape gardening is the one art in which we possess and use the living things themselves and not mere representations of them. The title, landscape gardener arose more than a century ago to designate the new art which aimed to give landscape like effects to gardens. It signifies the enlargement of mere gardening into complete harmony with nature. Before the advent of this new art, gardens were formal in their dominant features. Their chief value was to augment the architectural features in the scenes of which they became a part.
Citation: Troutman, Virginia. The need of landscape gardening. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Landscape Gardening; Home Decoration; Natural Beauty; Home Maintenance; Theses